Ketidaktepatan Sasaran Program KIP Kuliah dan Dampaknya terhadap Akses Pendidikan Tinggi - Ciek Julyati Hisyam; Ahmad Zakaria; Jalmi Katulistiwa; Lutfian Ahmad; Fatihah Putri Surya; Zahra Huseinah (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
The Indonesia Smart Card for Higher Education (KIP Kuliah) program is a government initiative aimed at expanding access to higher education for students from economically disadvantaged families. However, various reports indicate that the program's implementation has not always reached its intended beneficiaries, leading to concerns regarding targeting accuracy and the equitable distribution of educational assistance. This study examines the issue of mistargeting in the KIP Kuliah program and its impact on access to higher education. Using a qualitative descriptive approach based on literature review, the study analyzes policy documents, previous research, government reports, and relevant academic publications. The findings reveal that inaccuracies in beneficiary selection are influenced by weaknesses in socioeconomic data validation, administrative inconsistencies, and limited monitoring mechanisms. Consequently, eligible students may fail to receive financial support, while some ineligible recipients continue to benefit from the program. These conditions reduce the effectiveness of KIP Kuliah in promoting educational equity and limiting socioeconomic disparities in higher education participation. Strengthening data integration, improving verification procedures, and enhancing transparency and accountability are essential to ensure that educational assistance reaches deserving students and contributes to equitable access to higher education in Indonesia.